Os efeitos da matéria em neutrinos de supernovas - Martins , Bianca B.; Holanda, Pedro C. (Cadernos de Astronomia, 2024)
Neutrino emissions are fundamental to the formation of supernovae, however, the collapse of the stellar core and theeffects of interactions between particles in this high-density environment are not completely understood. Therefore, thecurrent work aims to study the relationship between neutrinos and supernovae due to gravitational collapse and explorehow interactions between neutrinos and the environment affect their propagation. In this sense, the behavior of neutrinosin stellar matter is modeled according to plane wave and density matrix formalisms, such that the neutrino evolutionequations are analytically deduced. In this way, the occurrence of Mikheyev-Smirnov-Wolfenstein (MSW) and collectiveeffects on supernova neutrinos is evident.
Keywords: Supernovae neutrinos; MSW effect; flavor conversions